Organization and accounting of operations with give-and-take raw material in accordance with international financial reporting standards - N. N. Batishcheva; E. A. Posnaya; A. S. Chuykov (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the article is to propose measures for the organization and accounting of operations with customer-supplied  raw  materials  in  accordance  with  current  International  Financial  Reporting Standards (IFRS). The materials of the study were examples of accounting for operations with give-and-take raw materials at enterprises of the Russian Federation. The study used analysis, synthesis, induction and deduction as research methods. The procedure for carrying out operations with give-and-take raw materials is actually determined by domestic legislation only in terms of their taxation, and mainly the results of the release of excisable products from such raw materials. Nevertheless, the conduct of such operations in our country is prohibited, yet it is a common phenomenon, including those often encountered in foreign economic activity. The article deals with the organization of operations with raw materials supplied by the customer, accounting and tax accounting of such operations, taking into account certain recommendations of IFRS. The result of the study can be considered a calculation within the framework of a conditional numerical example with a proposal for a variant of accounting for operations with give-and-take raw materials, which provides for all possible options for settlements between payers of income tax and VAT. The result of the study is the possibility of introducing all existing options for settlements between payers of income tax and VAT into the organization of accounting for operations with raw materials, which is clearly demonstrated in the text of the study.